Growth performance, digestive capacity and intestinal health of juvenile spotted seabass (Lateolabrax maculatus) fed dietary laminarin supplement - Qin, Huihui; Long, Zhongying; Ma, Jianrong; Kong, Lumin; Lin, Hao; Zhou, Sishun; Lin, Yi; Huang, Zhangfan; Liu, Longhui; Li, Zhongbao (Frontiers in Marine Science, 2023)
Laminarin has antioxidant and immunomodulatory properties and favorably impacts gut microbial composition, providing a potential solution for the treatment of intestinal diseases in fish. The aim of this study was to investigate the effects of laminarin on the growth and intestinal health of juvenile spotted seabass, Lateolabrax maculatus. A total of 450 juveniles (initial body weight: 7.14 ± 0.10 g) were randomly divided into 6 groups with 3 replicates per group and 25 fish per replicate. Six diets were prepared with laminarin supplementation at doses of 0% (Control), 0.4% (P0.4), 0.8% (P0.8), 1.2% (P1.2), 1.6% (P1.6), and 2% (P2). Each group was fed the corresponding diet for 8 weeks. The results indicated that dietary laminarin supplementation of 0.4-1.6% enhanced the specific growth rate (SGR), weight gain rate (WGR), and feed conversion ratio (FCR) of juvenile spotted seabass, and the difference was significant in the P0.8 group (P<0.05). Significantly higher intestinal amylase activity was measured in P0.8 compared with the control group. Trypsin activity was significantly increased in P0.4 and P0.8 groups in contrast to the control (P<0.05). Lipase activity was significantly increased in P0.4, P0.8, P1.6, and P2 groups in contrast to the control (P<0.05). Total antioxidant capacity was significantly increased in the P0.8, P1.2, and P1.6 groups compared to the control group (P<0.05). The P0.8 group exhibited significant increases in reduced glutathione, alkaline phosphatase, and lysozyme levels (P<0.05), whereas the concentrations of diamine oxidase and D-lactate were significantly decreased (P<0.05). Furthermore, intestinal villus height, villus width, and crypt depth were significantly increased in P0.8 and P2 groups (P<0.05), and muscular thickness was significantly increased in the P1.2 group (P<0.05). Intestinal microbial analysis revealed that the alpha diversity of the laminarin supplemented groups was significantly higher than that of the control group. Moreover, the abundance of intestinal beneficial bacteria Lactobacillus and Klebsiella in P0.4 and P0.8 groups was significantly increased (P<0.05), indicating that laminarin altered the composition of intestinal flora and the abundance of dominant bacteria, with a low dose being more conducive to the formation of beneficial bacteria. In conclusion, dietary laminarin supplementation can improve the growth performance and intestinal function of juvenile spotted seabass. Based on the regression analyses of weight gain rate and specific growth rate, the optimal supplemental level of laminarin was estimated to be 0.97% and 0.98%, respectively.